Peluang Dan Tantangan Dalam Membangun Bisnis Kerajinan Kulit Online Studi Kasus Koodoo Company - Muhammad Azmi Al Mutawakkil; Melani Putri Utami; Razak Fariz Maulana (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2024)
This research is based on the growth of the phenomenon of online shopping through Instagram social media which continues to increase from time to time. Entrepreneurs today are expected to utilize Instagram social media to promote their products, in accordance with the demands of the times. This research aims to identify opportunities and challenges in developing an online business with a case study on Koodoo Company. This research adopts a qualitative approach with a case study method to identify, investigate, and discuss issues in depth with the business owner. In this study, the findings show that there are various opportunities that can be utilized in building an online business, such as potential market growth and consumer penetration through digital platforms. The implications of this scientific work can provide deep insights for online business players, especially through a case study involving Koodoo Company. By understanding the opportunities that exist, companies can design more effective strategies to exploit the digital market.